COVID-19 mass vaccination – an illustration of the impact of syringe choice on the effectiveness of mass vaccination campaigns. Issue 1 (31st December 2022) - Roseline, Mazet; Luc, Choisnard; Julien, Leenhardt; Olivier, Epaulard; Etienne, Brudieu; Pierrick, Bedouch
ABSTRACT: In order to optimise the operational implementation of mass vaccination policies, it is critical to consider not only the supply of vaccines as well as each element of the vaccination process. This study, which was conducted in a vaccination center clearly shows how the choice of a syringe reference used during the COVID-19 vaccination campaign influences the number of vaccine doses available. The results appear to be closely related to the type of vaccine used (COMIRNATY® and SPIKEVAX®). In this context, the choice of the right reference of syringe has major economic and organisational consequences on a global scale.